Effective Strategies in the Management of Guidance and Counseling Implementation in Schools - Ice Desvikayati; Firman; Neviyarni S; Muhammad Asyraf Che Amat (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
The management of Guidance and Counseling (BK) implementation in schools has a strategic role in supporting the optimal development of student potential. This research aims to analyze effective strategies in the management of guidance and counseling implementation based on literature studies from various scientific articles. Using the literature study method, this research examines the concepts, practices, and challenges in the management of guidance and counseling in schools. The results show that effective BK management involves optimizing all resources, such as educators, infrastructure, funds, and information systems, by referring to the POAC principle (Planning, Organizing, Actuating, Controlling) as stipulated in Permendikbud Number 111 of 2014. The competence of counseling teachers is an important element to ensure that counseling services are relevant to students' needs, while inter-stakeholder collaboration and the fulfillment of adequate infrastructure are key to the success of the counseling program. Continuous evaluation is also needed to improve the effectiveness of counseling services. This study concludes that the implementation of planned and systematic management strategies can support the implementation of more effective counseling, thus making a significant contribution to the development of students' character, achievement and skills. Thus, counseling services can be an important pillar in achieving national education goals.